Linguistic Variation, Discourse Analysis, and Deaf Education: Case Studies from ISL. (23rd September 2022) - Cohen-Koka, Shirit; Nir, Bracha; Meir, Irit
Abstract: Variation in language has been acknowledged as central to the characterization of spoken and written discourse. Speakers' ability to change and adjust language according to the communicative circumstances is a prominent factor that demonstrates their linguistic literacy and skill. Nonetheless, few studies have explored the characterization of discursively motivated variation in sign languages, and little is known about the topic. The purpose of the current study is to present features of variation in Israeli Sign Language as they appear in two discourse types—narrative versus expository texts. We present this aspect of linguistic literacy as it is expressed in two case studies of two adult signers in two domains: sign parameters and the use of signing space. The findings reveal a discourse type effect on the way that these aspects are expressed and highlight the importance of discourse and linguistic knowledge to educators of deaf students.